Different regulation of stellar metallicities between star-forming and quiescent galaxies – insights into galaxy quenching - Baker, William M; Maiolino, Roberto; Bluck, Asa F L; Belfiore, Francesco; Curti, Mirko; D’Eugenio, Francesco; Piotrowska, Joanna M; Tacchella, Sandro; Trussler, James A A (Monthly notices of the Royal Astronomical Society, 2024)
ABSTRACT One of the most important questions in astrophysics is what causes galaxies to stop forming stars. Previous studies have shown a tight link between quiescence and black hole mass. Other studies have revealed that quiescence is also associated with ‘starvation’, the halting of gas inflows, which results in the remaining gas being used up by star formation and in rapid chemical enrichment. In this work, we find the missing link between these two findings. Using a large sample of galaxies, we uncover the intrinsic dependences of the stellar metallicity on galaxy properties. In the case of star-forming galaxies, stellar metallicity is primarily driven by stellar mass. However, for passive galaxies, the stellar metallicity is primarily driven by the stellar velocity dispersion. The latter is known to be tightly correlated with black hole mass. This result can be seen as connecting previous studies, where the integrated effect of black hole feedback (i.e. black hole mass, traced by the velocity dispersion) prevents gas inflows, starving the galaxy, which is seen by the rapid increase in the stellar metallicity, and leading to the galaxy becoming passive.